2012
DOI: 10.3758/s13414-012-0280-5
|View full text |Cite
|
Sign up to set email alerts
|

Competition-strength-dependent ground suppression in figure–ground perception

Abstract: Figure-ground segregation is modeled as inhibitory competition between objects that might be perceived on opposite sides of borders. The winner is the figure; the loser is suppressed, and its location is perceived as shapeless ground. Evidence of ground suppression would support inhibitory competition models and would contribute to explaining why grounds are shapeless near borders shared with figures, yet such evidence is scarce. We manipulated whether competition from potential objects on the ground side of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…We take these data as neural evidence that suppressive competition underlies the perception of a single object. The results show that greater competition for object status from regions ultimately perceived as grounds produces greater suppression of the ground, supporting previous behavioral data (Salvagio et al, 2012). The same pattern was evident across V1, V2, and V4.…”
Section: Experiments 1 Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We take these data as neural evidence that suppressive competition underlies the perception of a single object. The results show that greater competition for object status from regions ultimately perceived as grounds produces greater suppression of the ground, supporting previous behavioral data (Salvagio et al, 2012). The same pattern was evident across V1, V2, and V4.…”
Section: Experiments 1 Discussionsupporting
confidence: 88%
“…If it is, that will be consistent with the hypothesis that feedback from suppressive competition at higher levels modulates responses in lower-level brain regions. Consistent with this feedback hypothesis, Salvagio et al (2012) reported behavioral evidence of competitionmediated suppression for targets shown on grounds but not for targets shown on figures, even though the distance between targets on figures vs. grounds was less than 1 o of visual angle.…”
Section: Competition-mediated Ground Suppression !mentioning
confidence: 71%
See 3 more Smart Citations